Post-Traumatic Growth Among Exonerees: Exploring Transformative Experiences After Incarceration - Panuccio, Elizabeth; Shlosberg, Amy; Nowotny, Jordan (The Wrongful Conviction Law Review, 2022)
Exonerees face numerous barriers to reintegration following their release from wrongful imprisonment. To cope with the challenges they face after exoneration, they draw support from a wide range of external and internal resources, assisting them on their path towards self-sufficiency and resilience. In a study about life after exoneration through in-depth interviews with 26 exonerees, we explored the challenges of reentry for exonerees as well as strategies for success. Although none of the exonerees in our study reported finding closure (and most felt it was not attainable), some experienced what has been described in the academic literature as post-traumatic growth, indicating that although the damage wrought by the injustice of wrongful conviction and incarceration cannot be fully healed, some individuals have transformed their experiences into positive personal accomplishments. In this paper, we highlight the transformative experiences of exonerees as they re-established their lives post-release and consider how systems can provide the resources necessary to support post-traumatic growth.